Efeitos dos exercícios do Método Pilates sobre a distância inter-retos abdominais e queixas de assoalho pélvico em gestantes: estudo clínico randomizado controlado - Gonçalves, Rejane Amélia Reis (2024)
Introduction: It is known that it is extremely important that pregnant women are encouraged to practice physical exercise and the Pilates Method has become a popular option for physical exercise during pregnancy. However, little is known about the effects of the method on abdominal inter-rectus separation and complaints of pelvic floor dysfunction during the gestational period. Objectives: To evaluate the effects of a Pilates Method exercise protocol on abdominal inter-rectus distance (DIR) and complaints of discomfort related to the pelvic floor in pregnant women. Method: Randomized controlled clinical trial with parallel randomization, single blind and hidden allocation in which 42 pregnant women were included between the 18th and 21st gestational weeks. Participants were randomized into two groups: Pilates Group and Control Group. The participants in the first group performed a Pilates Method exercise protocol and the second group performed global exercises, without guidance for abdominal activation. In both groups, the intervention was carried out for 12 weeks, twice a week. Before and after, participants were assessed for IRD using ultrasound and for pelvic floor discomfort using the Pelvic Floor Bother Questionnaire (PFBQ). The repeated measures ANOVA test, with Tukey's post-roc test, was used for data analysis. Results: A group-time interaction was not observed for the DIR variable when evaluated at rest in the supra-umbilical region [F (1,40)=1.88; p=0.178] and infra-umbilical [F(1.40)=1.69; p=0.202]. The same happened when analyzing the DIR values in the supra-umbilical region with the participant in trunk flexion [F(1,40)=0.393); p=0.534] and when analyzing the values of the PFBQ questionnaire [F (1.40)=1.47; p=0.232]. Only when analyzing the DIR in the infra-umbilical region with the pregnant woman in trunk flexion, a group-time interaction was observed [F (1,40)=7.19; p=0.011]. Tukey's post-hoc test demonstrated that there was a greater increase in DIR in the Control Group when compared to the Pilates Group, with a high effect size. Conclusion: The intervention using the Pilates Method in pregnant women promoted a reduction in DIR only in the infra-abdominal measurement in flexion. There was no difference when compared to the group that performed global exercises for the other outcomes.